Risk factors for SARS-CoV-2 infection in primary and secondary school students and staff in England in the 2020/2021 school year: a longitudinal study. (March 2023) - Nguipdop-Djomo, Patrick; Oswald, William E; Halliday, Katherine E; Cook, Sarah; Sturgess, Joanna; Sundaram, Neisha; Warren-Gash, Charlotte; Fine, Paul EM; Glynn, Judith; Allen, Elizabeth; Clark, Taane G.; Ford, Benjamin; et al.
Highlights: Schools are key sites with potential for effective transmission of SARS-CoV-2. One of the largest research studies worldwide of SARS-CoV-2 in students and staff. Risk associated with public transports in Autumn 2020 and infections in household. No observed association with social contact pattern between students and staff. Schools can remain safely open with low transmission when mitigations are in place. Abstract: Objectives: Investigate risk factors for SARS-CoV-2 infections in school students and staff. Methods: In the 2020/2021 school year, we administered polymerase chain reaction, antibody tests, and questionnaires to a sample of primary and secondary school students and staff, with data linkage to COVID-19 surveillance. We fitted logistic regression models to identify the factors associated with infection. Results: We included 6799 students and 5090 staff in the autumn and 11, 952 students and 4569 staff in the spring/summer terms. Infections in students in autumn 2020 were related to the percentage of students eligible for free school meals. We found no statistical association between infection risk in primary and secondary schools and reported contact patterns between students and staff in either period in our study. Using public transports was associated with increased risk in autumn in students (adjusted odds ratio = 1.72; 95% confidence interval 1.31-2.25) and staff. One or more infections in the same household during either period was the strongest risk factor for infection in students and more so among staff. Conclusion: Deprivation, community, and household factors were more strongly associated with infection than contacts patterns at school; this suggests that the additional school-based mitigation measures in England in 2020/2021 likely helped reduce transmission risk in schools.